2007
DOI: 10.1177/1742395307079192
|View full text |Cite
|
Sign up to set email alerts
|

The impact of angina and cardiac history on health-related quality of life and depression in coronary heart disease patients

Abstract: Objective-To prospectively examine the contribution of angina and cardiac history to healthrelated quality of life (HRQoL) and depression in cardiac patients, over 6 months posthospitalization.Methods-Participants were myocardial infarction (MI), percutaneous coronary intervention (PCI), or coronary artery bypass grafting surgery (CABG) out-patients under the age of 70. One hundred and seventy one patients consented to participate, with 121 patients retained 6 months later (71% response rate). The impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
1
33
0
4
Order By: Relevance
“…Dispnea [11][12][13], weakness [12][13] and sleeping problems more frequent in women than in men [5][6][7][8][9][10][11][12][13][14][15][16][17]. The results of other investigations as a principal…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Dispnea [11][12][13], weakness [12][13] and sleeping problems more frequent in women than in men [5][6][7][8][9][10][11][12][13][14][15][16][17]. The results of other investigations as a principal…”
Section: Introductionmentioning
confidence: 86%
“…According to the results of investigations it was determined that HRQL among the patients was disordered and lower and the main reason for that was the presence of the chest pain or discomfort and the lowering of the overall physical function [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of a lack of CSE, depressed patients can develop maladaptive coping strategies such as behavioral disengagement and avoidance [33] which may translate into a lower motivation for self care and medication adherence [34]. Given that previous studies have demonstrated that effective management of depression reduces further episodes of chest discomfort, ischemic events and use of medical resources [7], there remains a great need to recognize and treat depression when it develops in patients hospitalized for CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of self efficacy in CVD have been demonstrated to be better predictors of outcomes including the use of analgesia, physical activity, and return to work than other variables such as age or medical status [3]. Following an acute coronary event, patients are suddenly confronted with a number of difficult challenges and questions, including the imposition of lifestyle changes, the future management of any recur-ring chest pain and uncertainty about their health status in the future [7]. CSE is particularly important in these patients as the idea of cardiac self management can often be foreign to many patients who have previously expected that their conditions would be solely managed by their physicians, and indeed may be linked to the person seeing their own past behaviours as causative, leading to denial or other maladaptive behaviours [8].…”
Section: Introductionmentioning
confidence: 99%
“…Alors que certaines ont évalué spécifiquement la qualité de vie reliée à la santé (Aparecida Spadoti Dantas & Aparecida Ciol, 2008;Lie, Arnesen, Sandvik, Hamilton, & Bunch, 2009;Martin et al, 2007;Mûller-Nordhorn et al, 2004;Noms & King, 2009;Rantanen et al, 2008Rantanen et al, , 2009Van Jaarsveld, Sanderman, Miedema, Ranchor, & Kempen, 2001;Unsar, Sut, & Durna, 2007;Worcester et al, 2007), d'autres ont plutôt mesuré de façon conjointe la qualité de vie reliée à la santé et la santé psychologique (soit la dépression et/ou l'anxiété) chez ces patients (Beck, Joseph, Belisle, & Pilote, 2001;Burg, Benedetto, Rosenberg, & Soufer, 2005;De Jonge, Spijkerman, van den Brink, & Ormel, 2006;Faller et al, 2007;Fauerbach et al, 2005;Goyal, Idler, Krause, & Contrada, 2005;Gravely-Witte, De Gucht, Heiser, Grace, & Van Elderen, 2007;Hôfer et al, 2005;Lane, Carroll, Ring, Beevers, & Lip, 2001;Mallik et al, 2005;Mayou et al, 2000;Perski et al, 1998;Reid, Tueth, Handberg, & Nyanteth, 2006;Ruo et al, 2003;Spertus, McDonell, Woodman, & Fihn, 2000;Sullivan, LaCroix, Baum, Grothaus, & Katon, 1997;Tully, Baker, Turnbull, Winefield, 20 & Knight, 2009;Volz et al, 2011). De façon sommaire, ces études font ressortir que plusieurs sphères de la qualité de vie reliée à la santé subissent des dommages importants et que l'anxiété et la dépression sont associées négativement à la qualité de vie reliée à la santé chez les patients coronariens.…”
Section: Qualité De Vie Reliée à La Santé Et Maladies Cardiovasculairesunclassified